Software System Development to Diagnose Heart Diseases - Ferreira, Renan Yuji Koga; de Melloy, Guilherme Camargo Fabricio; Sakurayz, Fabio; Attrot, Wesley (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2019)
Many deaths are caused from heart diseases and several of them could be prevented with early detection. Many people do not have conditions to seek for a doctor or sometimes there are not enough physicians to attend them. In order to detect heart diseases we are developing an electrocardiogram feature extraction algorithm using wavelet transforms prioritizing a low computational cost. This algorithm will be integrated in an embedded system that is under development. This system is going to be accessible, portable and have low cost, because we intend to assist people, mostly those who live in precarious regions, that do not have a physician to attend them. To execute tests on our algorithm we will use the ECG records from MITBIH database and after that we will classify the heartbeats in order to detect anomalies on them.